(untitled) (Journal of Applied Science and Engineering A, 2024)
Plastic wastes rise annually as a result of the growing demand for synthetic materials, which contributes to their manufacture. There are four main ways to recycle waste polymer, with thermal treatment for fuel being the most favorable to the environment. In this study, the thermal processing of plastic wastes was investigated with an anaerobic pyrolysis apparatus, and their thermal degradation was evaluated by using the thermogravimetric apparatus. Additionally, the elemental composition was determined by an elemental analyzer, n-alkanes were identified by gas chromatography with flame ionization detection/electron capture detector (GC-FID/ECD), and the hydrocarbons functional group was analyzed by Fourier transform infrared spectroscopy (FTIR). We pyrolyzed the most widely utilized polymers, including polypropylene (PP), low-density polyethylene (LDPE), and high-density polyethylene (HDPE), at temperatures as elevated as 500°C to obtain plastic pyrolysis oil (PPO). Then PPO was distilled into initial boiling point (IBP)-200°C (gasoline-like fuel), 200-350°C (diesel-like fuel), and over 350°C fraction (residue), and the technical features of each fraction were compared to the MNS 0217:2006 and MNS 6861:2020 standards. Diesel-like fuel (DLF) derived from LDPE consists of the n-alkane hydrocarbons with C8–C23 identified by flame ionization detection (FID) data; C10–C17 represented more than 80% of them. The hydrotreatment results revealed that the diesel-like fraction’s nitrogen (N) and sulfur (S) amounts could have reduced from 0.06% to 0.01% and from 0.78% to 0.29%, respectively. In conclusion, it could be done to generate a product with a more stable hydrocarbon content from plastic wastes for fuel.